Declarations of Incompatibility, Dialogue and the Criminal Law. (March 2014) - Davis, Fergal F.; Mead, David
The past 30 years have seen the development of 'New Commonwealth' forms of judicial review. These models of review are characterized by an emphasis on institutional dialogue over either legislative or judicial supremacy. Thus, instead of giving courts a strike down power, dialogic review grants courts the power to declare legislation 'incompatible' with human rights norms while leaving the final say on the legislation with the legislature. This article explores the potential for controversy when such a non-binding mechanism is employed in the arena of the criminal law. In particular, it focuses on the Northern Irish case of R v McR and the Australian case of Momcilovic v the Queen . These cases demonstrate the difficulties associated with the operation of dialogic review in the criminal law.